Higher classification of New World parrots (Psittaciformes; Arinae), with diagnoses of tribes - Schodde, Richard; Remsen, J. Jr. V.; Schirtzinger, Erin E.; Joseph, Leo; Wright, Timothy F. (Zootaxa, 2013)
We offer here a diagnosed higher-level classification of New World parrots to reflect relationships inferred from a consensus of recent DNA-based phylogenies and morphological and behavioral studies. General understanding of the position of New World parrots among the Psittaciformes through the later 20th century stems from Smith’s (1975) exhaustive review of structural morphology and behavior, which supplanted previous hypotheses (e.g. Verheyen 1956; Boetticher 1959; Brereton 1963; Wolters 1975). In his study, which covered over 54 genera, including 20 of the roughly 31 from the New World (Collar 1997; Dickinson 2003), Smith (1975) concluded that the New World parrots were monophyletic. Moreover, he considered the New World parrots sufficiently divergent from other parrots to be accorded subfamily rank because they share several unique morphological and behavioral characters, including imperforate neonatal ear canals, double-sided “dyck texture” (Dyck 1971) pigmentation of remiges, lack of cutaneous pigmentation, and one-legged copulatory stance.